(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Correction: Table 1 and Table 2 were omitted in from the PDF of this article. On 29th April 2015 the two tables were included in the PDF and the page numbers were changed from 151-158 to 151-160. Eight groups of zooplankton were found at Sitakunda coast, Chittagong, northeastern part of the Bay of Bengal during January to June 2007. The identified groups were Appendicularia (2.46%), Chaetognatha (2.45%), Cladocera (2.31%), Copepoda (26.05%), Ctenophora (5.86%), Crustacean zooplankton (21.64%), Ichthyoplankton (17.77%) and Meroplankton (21.45%). Abundance of zooplankton varied from 413 to 7730 individuals/m3.Mangrove vegetate area (station- VI) has the highest abundant possibly due to the organic and inorganic matters dissolved in the water while ship breaking area (station- IV) has the lowest abundant. Zooplankton population was significantly (p>0.05) higher in the mangrove vegetate area than the fishermen community area and ship breaking area. The mangrove vegetate area has the highest composition (57.06%) of zooplankton than the fishers community area and ship breaking area (29.77% and 13.16%, respectively). Calanus sp. (12.29%) belonging to Copepods and fish eggs (9.25%) belonging to Ichthyoplankton were the most abundant and Oikopleura albicans (0.66%) from Appendicularia, Metapenaeus brevicornis (0.71%) and Metapenaeus monoceros (0.90%) belonging to Crustacean larvae were the lowest abundant species found at three major investigated area. Res. Agric., Livest. Fish.2(1): 151-160, April 2015